Mass transfer and hydrodynamic characteristics in a co-current downflow contacting column - Dursun, G; Orhan, R; Akosman, C (John Wiley & Sons Ltd, 2003)
Hydrodynamic and mass transfer characteristics of water-air system in a co-current downflow contacting column (CDCC) were studied for various nozzle diameters at different superficial gas velocities and liquid re-circulation rates. Gas hold-up and liquid-side mass transfer coefficient increased with increasing superficial gas velocity and liquid flow rate but decreased with increasing nozzle diameter. It is shown that correlations developed, which are based on liquid kinetic power per liquid volume present in the column, and superficial gas velocity explains gas hold-up and the mass transfer coefficient within an error 20% for all gas and liquid flow rates and nozzle diameters used. The constants of correlations for gas hold-up and mass transfer coefficient were found to be considerably different from other gas-liquid contacting systems. (C) 2003 Society of Chemical Industry.
Keywords: gas hold-up; mass transfer; k(L)a; co-current downflow contacting column (CDCC); correlation